DETERMINATION OF FINANCIAL STABILITY OF BANKS IN INDONESIA - ikawulandari; Hwihanus ((JRAMB) Jurnal Riset Akuntansi Mercu Buana, 2025)
This study aims to determine the effect of green banking practices, management characteristics, bank size, bank age, and public ownership on bank financial stability. Financial stability is a condition where a bank is able to carry out its financial intermediation function while maintaining profitability. The study was conducted on banks in Indonesia listed on the Indonesia Stock Exchange from 2017 to 2023. The sample selection used purposive sampling and obtained 12 companies. Data analysis was performed using regression with the SMART PLS Ver 4 analysis tool. The results showed that management characteristics and bank size have a positive effect on financial stability. Green banking practices, public ownership, and bank age do not affect financial stability. These findings emphasize the importance of improving managerial quality and competence in maintaining financial stability. Banks need to strengthen management capacity, especially in strategic decision-making, risk management, and sustainable financial product innovation. In addition, increasing asset size and operational efficiency can be a strategy to strengthen the position of long-term financial stability